Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

fitch_fan

  • 4 years ago

4x-(2x+3)=7

  • This Question is Closed
  1. Brunna
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    4x -(2x+3) = 7 4x -2x -3 = 7 2x = 7+3 2x= 10 x = 10/2 x = 5

  2. fitch_fan
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    i dont get 4x -2x -3 = 7 why do you subtract 3

  3. Brunna
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    You need multiply all terms for -: -(2x +3 ) = -(+2x) - (+3) = -2x -3 Did you understand?

  4. zrsmith
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    -(2x+3) is the same thing as -1(2x+3), then multiply -1*2x = -2x, and then multiply -1*(+3) = -3

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy